Primary heating of charge during electric furnace smelting of cast iron and steel - L. E. Rovin; S. L. Rovin; L. S. Shumanskaya (Литьë и металлургия)
А problem of reduction of specific electric energy consumption during electric furnace smelting of cast iron and steel is examined. Analysis of known methods of primary heating of charge is carried out, variants of single- and two-stage installations of gas heating of metal charge are suggested.